The Biological Basis of Learning: Neuroeducation Through Simulation. (April 2015) - Rodgers, David L.
Background: Brain-based learning (BBL), also referred to aseducational neuroscience, examines learning as a biological process. Teaching to support BBL requires blending of understanding of neuroscience with the practice of education. With BBL, the learning environment is designed to enhance the brain's natural ability to learn. Aim: This manuscript describes thefundamentals of brain-based learning, translates the basic tenets of BBL to thesimulation learning environment, and presentspractical application strategies for simulation-based learning. Method: Focusing on the work of Renate and Geoffrey Caine, this article examines their approach to BBL, including the threecore elements of brain-based learning experience:orchestrated immersion in complex environments, relaxed alertness, andactive processing . The three elements of the Caine and Caine model are well-embedded in the larger BBL literature and have particular utility with simulation-based education. Results: The three core elements of BBL have direct application tosimulation as a teaching and learning practice. This paper presents several specificstrategies designed to enhance both the simulation eventexperience and thedebriefing . Conclusion: The simulation learning environment can be adapted to capitalize on the tenets of BBL. Severalinstructional strategies are available toenhance thebiological process of learning while utilizing simulation-based learning practices.